From soil to symbiosis: Uncovering genetic diversity of lentil-nodulating rhizobia in Iranian agriculture - Hossein Kari Dolatabad; Vahid Alah Jahandideh Mahjenabadi; Kazem Khavazi (The Microbe)
The primary objective of the present study was to elucidate the genetic diversity of lentil-nodulating rhizobia in Iran, utilizing an amalgamation of molecular techniques. A total of 116 rhizobia strains were isolated from soil and nodule samples collected from lentil-growing regions of Iran, and their genetic makeup was analyzed using BOX-PCR and RAPD techniques, as well as PCR/RFLP analysis of the 16S–23S IGS region and sequencing of 16S rRNA and glnII genes. The results showed that the rhizobia strains belonged to two different species, Rhizobium leguminosarum and R. laguerreae, with R. leguminosarum being the more predominant species. The strains of R. leguminosarum and R. laguerreae were grouped into different classes using BOX and RAPD techniques, which indicate their distinct genetic composition and evolutionary relationships. The genetic diversity was influenced by geographic location, indicating that different regions may have unique rhizobia populations with distinct genetic characteristics. The high level of genetic diversity observed among the lentil-nodulating rhizobia in Iran underscores the importance of using locally adapted rhizobia strains in lentil cultivation.